MSXJ, hybrid of papaya without carpellody for southeastern Mexico - Mirafuentes Hernández Felipe; Santamaría Basulto Felipe (Revista Mexicana de Ciencias Agrícolas, 2018)
Papaya (Carica papaya L.) is a fruit grown in many tropical and subtropical regions, develops best where temperatures remain 21 to 32 °C. When f lowering coincides with temperatures above 35 °C abortion of flowers and production of deformed fruits occurs because the stamens are fused to the carpels of the ovary, causing Carpellody fruits that have no commercial value, thus low yielding. MSXJ is a hybrid of papaya that tolerate temperatures above 35° during bloom producing well-formed fruits with an average weight of 1.5 kg, red and f irm f lesh. Because it has low frequency of carpellody fruits and fruit drop is a very productive cultivar. The parents are J hybrid, a landrace of papaya of vigorous bearing with no production of carpellody fruits and MST, a cultivar selection of Maradol of intermediate bearing. The hybrid MSXJ can produce between 31 and 41 elongated fruits per plant yield between 50 and 63 kg per plant so that productivity can be from 100 to 125 t ha-1. The fruits of hermaphrodite plants are of good quality elongated without deformation, developing intermediate size between 25 and 29 cm long, 10-13 cm in diameter at the widest part and 1.4 to 1.7 kg. The flesh is firm; it has a strength of 8-12 N and total soluble solids content of 10.5 to 11 °Brix.